Radiotherapy or Autologous Stem-Cell Transplantation for Primary CNS Lymphoma in Patients Age 60 Years and Younger: Long-Term Results of the Randomized Phase II PRECIS Study. Issue 32 (10th November 2022) - Houillier, Caroline; Dureau, Sylvain; Taillandier, Luc; Houot, Roch; Chinot, Olivier; Moluçon-Chabrot, Cécile; Schmitt, Anna; Gressin, Rémy; Choquet, Sylvain; Damaj, Gandhi; Peyrade, Frédéric; Abraham, Julie; et al.
Abstract : Clinical trials frequently include multiple end points that mature at different times. The initial report, typically based on the primary end point, may be published when key planned co-primary or secondary analyses are not yet available. Clinical Trial Updates provide an opportunity to disseminate additional results from studies, published in JCO or elsewhere, for which the primary end point has already been reported. We previously reported the results of a randomized phase II study in patients with newly diagnosed primary CNS lymphoma (age 18-60 years). Patients were treated with high-dose methotrexate-based induction chemotherapy followed by whole-brain radiotherapy (WBRT) or high-dose chemotherapy (thiotepa-busulfan-cyclophosphamide) with autologous stem-cell transplantation (ASCT). The median follow-up was 33 months. In this report, we provide long-term data (median follow-up, 8 years) regarding the outcomes and toxicities. Fifty-three and 44 patients received induction chemotherapy followed by WBRT or ASCT, respectively. Their 8-year event-free survival from random assignment was 67% and 39% in the ASCT and WBRT arms, respectively ( P = .03), with a significantly lower risk of relapse after ASCT (hazard ratio, 0.13; P < .001). One third of patients who relapsed after WBRT were alive after salvage treatment. Five and four patients died of ASCT and WBRT-related toxicities, respectively. The 8-year overall survival was 69% and 65% in the ASCT and WBRT arms, respectively (not significant). Balance (52% v 10%, P ≤ 0.001) and neurocognition (64% v 13%, P < .001) significantly deteriorated after WBRT compared with ASCT during the follow-up. This study shows that 40 Gy WBRT should be avoided in first-line treatment because of its neurotoxicity and suboptimal efficacy in reducing relapses while ASCT appears to be highly efficient in preventing relapses.